Эксплуатация газовых скважин - Ермилов О. М. Олег Михайлович; Алиев З. С. Загид Самедович; Ремизов В. В. Валерий Владимирович; Чугунов Л. С. Леонид Семенович (Москва, Наука, 1995)
Исключено из фонда НТБ ТПУ